The estimation of digestible protein in the small intestine of ruminants. The French system. - FLOROU-PANERI (Π. ΦΛΩΡΟΥ - ΠΑΝΕΡΗ), P. (Journal of the Hellenic Veterinary Medical Society, 2018)
The ruminants, as all animals, need to obtain a certain amount of dietary protein to satisfy their requirements in nitrogen. Until 1978, the system of digestible protein was employed in France to estimate both the nitrogen requirements of ruminants for their maintenance and/or production and the protein value of feedstuffs. This system, however, presents considerable disadvantages since it cannot distinguish the protein nitrogen from the non protein nitrogen. Moreover, this system does not take into account the microbial protein synthesis and the protein degradability in the rumen. It was for these reasons that French researchers start using from 1978 the system of digestible protein in the small intestine, i.e. the system P.D.I. for the estimation of the protein requirements of ruminants and the protein value of feedstuffs.